Pruritic Trichostasis Spinulosa: A Rare Variant - Vishal Gaurav; Mehul Tyagi; Chander Grover; Sonal Sharma (Wolters Kluwer Medknow Publications, 2024)
Trichostasis spinulosa is a disorder of hair follicles characterized by the retention of vellus telogen club hair, leading to the formation of comedo-like lesions. It usually presents over the face and is frequently asymptomatic. We report a 53-year-old female who presented with multiple itchy, discrete, bluish-black, 2-3 mm comedo-like follicular papules and pustules on her breast and lower abdomen for the past 2 years. In-vivo dermoscopy showed keratotic plugs with a tuft of hair. Extraction dermoscopy yielded a cystic structure filled with keratin and multiple vellus telogen club hairs. Histology showed a cyst lined by squamous epithelium containing abundant laminated keratinous debris and a vellus hair shaft. Truncal or breast involvement, as seen in the present case, is relatively rare, and can be pruritic, causing significant morbidity due to itching and secondary bacterial infections. Dermoscopy, especially ex-vivo extraction dermoscopy, can show diagnostic features and obviate the need for abiopsy.